Comparative 13C‐metabolic flux analysis indicates elevation of ATP regeneration, carbon dioxide, and heat production in industrial Saccharomyces cerevisiae strains. Issue 3 (25th May 2021) - Yatabe, Futa; Okahashi, Nobuyuki; Seike, Taisuke; Matsuda, Fumio
Abstract: Background: Various industrial Saccharomyces cerevisiae strains are used for specific processes, such as sake, wine brewing and bread making. Understanding mechanisms underlying the fermentation performance of these strains would be useful for further engineering of the S. cerevisiae metabolism. However, the relationship between the fermentation performance, intra‐cellular metabolic states, and other phenotypic characteristics of industrial yeasts is still unclear. In this study, 13 C‐metabolic flux analysis of four diploid yeast strains—laboratory, sake, bread, and wine yeasts—was conducted. Results: While the Crabtree effect was observed for all strains, the metabolic flux level of glycolysis was elevated in bread and sake yeast. Furthermore, increased flux levels of the TCA cycle were commonly observed in the three industrial strains. The specific rates of CO2 production, net ATP regeneration, and metabolic heat generation estimated from the metabolic flux distribution were two to three times greater than those of the laboratory strain. The elevation in metabolic heat generation was correlated with the tolerance to low‐temperature stress. Conclusion: These results indicate that the metabolic flux distribution of sake and bread yeast strains contributes to faster production of ethanol and CO2 . It is also suggested that the generation of metabolic heat is preferable under the actual industrial fermentation conditions. Graphical Abstract and Lay Summary: 13 C‐metabolic flux analysis of four diploid Saccharomyces cerevisiae strains—laboratory, sake, bread, and wine yeasts—was conducted to investigate the relationship between the intra‐cellular metabolic flux distribution, fermentation performance, and metabolic heat production. The metabolic flux level of glycolysis was elevated in bread and sake yeast while increased flux levels of the TCA cycle were commonly observed in the three industrial strains. The specific rates of CO2 production, and metabolic heat generation estimated from the metabolic flux distribution were two to three times greater than those of the laboratory strain that correlated with the tolerance to low‐temperature stress.